The adoption of chief diversity officers among S&P 500 firms: Institutional, resource dependence, and upper echelons accounts - Shi, Wei; Pathak, Seemantini; Song, Lynda Jiwen; Hoskisson, Robert E. (Human Resource Management, 2018)
The importance of workforce diversity has become a salient management concern given that demographic minorities comprise key sources of the workforce and consumers. As a result, some firms created chief diversity officer (CDO) positions to manage workforce diversity. This study takes a multitheoretic approach, drawing upon institutional, resource dependence, and upper echelons theories to explain firms' adoptions of this key position. Using Cox event history analyses based on a sample of S&P 500 firms, we find that, from an institutional theory perspective, firms are more likely to adopt CDOs when they are headquartered in legalized gay marriage states and the accumulative number of industry CDO adoptions is high. From a resource dependence perspective, we find that firm innovation intensity, diversification levels, transient institutional ownership, and industry female and African American employment bases can predict firms' adoptions of CDO positions. From an upper echelons explanation, we find that female top management team representation is positively associated with firms' adoptions of CDO positions.